Affirmative Action and Labor Markets - Smith, James P.; Welch, Finis (Journal of Labor Economics, 1984)
Affirmative action remains controversial. The controversy extends from the original antidiscrimination legislation and its interpretation to estimates of affirmative action's effect on the labor market. This paper provides a progress report on our recent efforts at detecting the effects of affirmative action on minority wages and employment. Although we find a substantial increase in wages for black men and black women over our sample period, the timing of these wage changes is surprising. Most of the wage gains came prior to 1974, before the establishment of an effective monitoring structure for affirmative action. Indeed, when the powers of the EEOC and OFCC are greatest, the wage effects for young blacks are somewhat perverse. Using EEO-1 reports we find a major shift in black employment toward firms most vulnerable to the monitoring and potential sanctions of the affirmative action programs. As with wages, the shift in minority employment came prior to the expansion of the powers and budgets of the EEOC and OFCC. We are surprised by the timing of these changes and are concerned about the quality of the EEO-1 reports.